2016
DOI: 10.1177/1460458216648477
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial effect of web-based information in fast-track surgery

Abstract: The psychosocial effects of web-based information have yet to be tested for patients joining a fast-track total hip arthroplasty programme. This study compared and evaluated the psychosocial impact of standard total hip arthroplasty programme, with and without supplementation with a web-based information platform (E-total hip arthroplasty programme). Totally, 299 patients were enrolled in an un-controlled, before-and-after study, 117 in the S-total hip arthroplasty programme group and 182 in the E-total hip ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It was decided to promote implementation by providing participants with easy access. This was decided as a previous study introducing a similar Web-based platform for patients undergoing total hip replacement found the access rate as low as 61% [38]. With reference to theories within implementation [39], attention was given toward easy access.…”
Section: Methodsmentioning
confidence: 99%
“…It was decided to promote implementation by providing participants with easy access. This was decided as a previous study introducing a similar Web-based platform for patients undergoing total hip replacement found the access rate as low as 61% [38]. With reference to theories within implementation [39], attention was given toward easy access.…”
Section: Methodsmentioning
confidence: 99%
“…No mediation of such behavior was needed. A previous study introducing a Web-based platform for patients undergoing total hip replacement found the access rate as low as 61% [23]. With reference to one of the main theories within implementation described by Everett M. Rogers in 1962 [24], it was decided to promote implementation and provide participants with easy access.…”
Section: The Internet Support Groupmentioning
confidence: 99%